Market responses to unexpected earnings of - Laura Schaffer, Laura Schaffer (My University, 2011)
The presence of a predictable share price response to a surprise in announced earnings by listed companies has been documented in US equity markets since 1968. This research investigated whether the presence of a positive or negative earnings surprise for companies listed on the JSE Securities Exchange resulted in an equivalent predictable share price response. The research was conducted on a sample of 112 companies listed on the JSE Securities Exchange between the period 1 February 2001 and 8 August 2007. The study analysed share price responses to 946 earnings surprise events over the three-day trading window around the actual earnings announcement date. Sell-side analyst earnings forecasts as published on INET Bridge were used as a proxy for the earnings expected by the market at the time of the company earnings announcement. The results of the event study showed a weakly positive share price response to a positive earnings surprise, the presence of which was not sustained once a few extreme values were excluded from the sample. The event study results for negative earnings surprises were more conclusive in showing no predictable significant share price response.
MBA - WBS
Keywords: Share price movements; Johannesburg Securities Exchange